GMMA Is a Versatile Platform to Design Effective Multivalent Combination Vaccines - Francesca Micoli; Renzo Alfini; Roberta Di Benedetto; Francesca Necchi; Fabiola Schiavo; Francesca Mancini; Martina Carducci; Elena Palmieri; Cristiana Balocchi; Gianmarco Gasperini; Brunella Brunelli; Paolo Costantino; et al. (Vaccines, 2020)
Technology platforms are an important strategy to facilitate the design, development and implementation of vaccines to combat high-burden diseases that are still a threat for human populations, especially in low- and middle-income countries, and to address the increasing number and global distribution of pathogens resistant to antimicrobial drugs. Generalized Modules for Membrane Antigens (GMMA), outer membrane vesicles derived from engineered Gram-negative bacteria, represent an attractive technology to design affordable vaccines. Here, we show that GMMA, decorated with heterologous polysaccharide or protein antigens, leads to a strong and effective antigen-specific humoral immune response in mice. Importantly, GMMA promote enhanced immunogenicity compared to traditional formulations (e.g., recombinant proteins and glycoconjugate vaccines), without negative impact to the anti-GMMA immune response. Our findings support the use of GMMA as a “plug and play” technology for the development of effective combination vaccines targeting different bugs at the same time.